COLONY COMPOSITION AND BIOMASS OF MACROTERMES GILVUS HAGEN (BLATTODEA: TERMITIDAE) IN INDONESIA - SUBEKTI, NIKEN; Widiyaningrum, Priyantini; Nandika, Dodi; Solihin, Dedy Duryadi (IIUM Engineering Journal, 2019)
ABSTRACT: There is no study conducted to investigate the composition and biomass of Macrotermes gilvus Hagen in natural forest ecosystem. This study aimed to analyze the colony composition and biomass of M. gilvus Hagen colony in natural forest and to evaluate the need of food of the species as well as factors affecting it. Research was conducted in Yanlappa Sanctuary, Bogor, West Java. Termites were surveyed by collecting individual M. gilvus Hagen from different colony at different size of mound, small (0 – 0.99 m), medium (1- 1.99 m), large (? 2 m) and then were measured the number of individuals, wet and dry body mass, ratio of dry or wet body mass, and the average of biomass. Results indicated that the small mount was dominated by workers, whereas the medium and the large nest was dominated by nymph. Mean of the termite biomass was 936 kg/ha2. Average of termite biomass collected from large mount was 949.8 kg/km2, medium mount was 605.2 kg/ha2 and small mount was about 537.5 kg/ha2. Factor affecting the biomass of subterranean termite M. gilvus Hagen are food source, energy efficiency, predators, and environment. The presence of termite mounds influences natural ecosystem, but that the type of mound plays a crucial role in determining the nature of the effects. ABSTRAK: Kajian tentang komposisi koloni dan biomas anai-anai tanah M. gilvus Hagen di hutan alam belum pernah dilakukan. Kajian ini bertujuan untuk menganalisis komposisi koloni dan biomas koloni anai-anai tanah M. gilvus Hagen di hutan alam dan menganalisa faktor-faktor yang mempengaruhi pemakanannya. Kajian ini dilakukan di Cagar Alam Yanlappa, Bogor, Jawa Barat. Hasil kaji selidik menunjukkan terdapat perbedaan koloni didasarkan pada ukuran tinggi sarang. Sarang kecil (0 – 0.99 m), sarang sedang (1- 1.99 m), dan sarang besar (? 2 m) dan ukuran berat basah, berat kering serta kadar berat basah atau berat kering, dan rata-rata biomas. Hasil kajian menunjukkan bahwa sarang kecil didominasi oleh koloni pekerja, sementara itu sarang serdahana dan sarang besar didominasi oleh koloni nympha. Rata-rata biomas yang ditemukan untuk sarang besar 949.8 kg/ha2, sarang serdahana 605.2 kg/ha2, dan sarang kecil 537.5 kg/ha2. Faktor-faktor yang mempengaruhi biomas anai-anai tanah M. gilvus Hagen adalah makanan, tenaga, pemangsa dan lingkungan. Kehadiran koloni anai-anai mempengaruhi ekosistem semulajadi, tetapi jenis koloni memainkan peranan penting dalam menentukan sifat kesannya.